2013
DOI: 10.1016/j.carbpol.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ionic liquid 1-ethyl-3-methylimidazolium acetate on the phase transition of starch: Dissolution or gelatinization?

Abstract: This work revealed that the interactions between starch, the ionic liquid 1-ethyl-3-methylimidazolium acetate ([Emim][OAc]), and water might contribute to the phase transition (gelatinization, dissolution, or both) of native starch at reduced temperature. Using mixtures of water and [Emim][OAc] at certain ratios (7.2/1 and 10.8/1 mol/mol), both the gelatinization and dissolution of the starch occur competitively, but also in a synergistic manner. At lower [Emim][OAc] concentration (water/[Emim][OAc] molar rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 53 publications
(60 reference statements)
9
57
0
Order By: Relevance
“…For RMS-E27, it appears that the sample was melting rather than gelatinizing, as it does not show a gelatinisation peak. This behaviour could be explained by an observation in a study by Mateyawa et al (Mateyawa et al, 2013) who showed that as the proportion of [Emim][OAc] increased, the blend dissolved prior to gelatinisation at low temperatures. Therefore, in the RMS-E27 sample here it is suggested that the starch had dissolved prior to processing, hence a high viscosity and high torque were observed initially The samples had subtle differences in their nature after mixing.…”
Section: Mixing Torquementioning
confidence: 99%
See 2 more Smart Citations
“…For RMS-E27, it appears that the sample was melting rather than gelatinizing, as it does not show a gelatinisation peak. This behaviour could be explained by an observation in a study by Mateyawa et al (Mateyawa et al, 2013) who showed that as the proportion of [Emim][OAc] increased, the blend dissolved prior to gelatinisation at low temperatures. Therefore, in the RMS-E27 sample here it is suggested that the starch had dissolved prior to processing, hence a high viscosity and high torque were observed initially The samples had subtle differences in their nature after mixing.…”
Section: Mixing Torquementioning
confidence: 99%
“…A study has been carried out to observe the mechanism of IL (in this case [Emim][OAc]) effects on different starches (Mateyawa et al, 2013). It is reported that IL actually behaves as a solvent rather than a gelatinisation agent as shown by DSC.…”
Section: Ionic Liquid/starch Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polyols (glycerol, glycol, sorbitol, etc) and nitrogen containing compounds (urea, ammonium and amines) as plasticizers are reported in the literature (Liu, Xie, Yu, Chen & Li, 2009;Xie, Halley & Averous, 2012 (Wilpiszewska & Spychaj, 2011;Liu & Budtova, 2013, Mateyawa et al, 2013Jordon, Scmidt, Liebert & Heinze, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The imidazolium based ionic liquids, are reported to be more efficient solvents for polysaccharides than NaOH-water system, dissolving more cellulose (20 % wt) and are reckoned to be better starting materials for fibres, films and aerogels (Kosan, Michels & Meister, 2008;Liu & Budtova, 2013;Remsing, Swatloski, Rogers & Moyna, 2006;Cai, Zhang, Guo). Recently, the dissolving and plasticizing ability of imidazolium based ionic liquids on starch, particularly, [Emim][OAc] (Wilpiszewska & Spychaj, 2011;Liu & Budtova, 2013;Mateyawa et al, 2013) …”
Section: Introductionmentioning
confidence: 99%